GENRE-BASED APPROACH AND VOCABULARY MASTERY ON STUDENTS’ RECOUNT TEXT WRITING SKILLS - Ilham Kurnia Sukma; Engliana Engliana (INFERENCE: Journal of English Language Teaching, 2019)
The purpose of this study was to find out the impact of genre-based approach and vocabulary mastery on students’ recount text writing skill. The population of the research is nine graders from private Islamic junior high school in Cikarang. The sample was taken from two private Islamic junior high schools. The method used in survey method. Data were collected through questionnaire dissemination techniques and test. Data analysis using the techniques of simple correlation coefficients and multiple correlations using Pearson’s formula are also assisted by using SPSS 20.0 version. Coefficient of determination and regression test are also using SPSS 20.0 version. Statistic test used was the t test and F test. The study was conducted in February to June 2019. The result of the study indicates that there are significant effects of genre-based approach and vocabulary mastery together on students’ recount text writing. It is proved by the score of Fo = 56,608 and Sig. 0,000 < 0,05. The data shows that genre-based approach and vocabulary mastery influence significantly and simultaneously on students’ recount text writing skill.